Municipal assessments versus actual sales prices in hedonic price studies - Mario Du Preez; Michael Sale (Journal of Economic and Financial Sciences, 2015)
In most hedonic price model studies, the actual sales price of a property is employed as the dependent variable in the parametric regression analysis. Although the use of this price is pervasive, alternatives to it do exist. One such alternative is the assessed property value, which is more readily available than the actual property price. The aim of this study is to compare implicit price estimates of property characteristics (both structural and locational) based on actual sales price data and assessed property values. To this end, a seemingly unrelated regression with two hedonic price equations is used, one which employs actual market prices as the dependent variable and the other which employs assessed values. The results show that the hypothesised influence of structural and locational housing characteristics on residential property prices is the same for assessed values, and actual market prices cannot be accepted. This finding should act as a caution for hedonic practitioners not to base their conclusions and recommendations solely on the use of assessed values in hedonic price models.